Beta-Blocker widrawal in chronic hearth failure a retrospective cross-sectional study in Manila. - Cajigas, Gian Adrian P.; Alcantara, Celeste Carmelle D.
The beta-blocker rebound phenomenon resulting from abrupt discontinuation presents significant clinical concerns, particularly due to the potential emergence of withdrawal symptoms. Despite this risk, there remains a lack of clear, standardized guidelines on appropriate tapering strategies in current clinical practice. This study aimed to evaluate the association between various beta-blocker deprescribing strategies and the occurrence of withdrawal symptoms among adult patients with chronic heart failure, while also describing patient demographics and deprescribing characteristics.